2019
DOI: 10.1093/mnras/stz1579
|View full text |Cite
|
Sign up to set email alerts
|

Average dark matter halo sparsity relations as consistency check of mass estimates in galaxy cluster samples

Abstract: The dark matter halo sparsity provides a direct observational proxy of the halo mass profile, characterizing halos in terms of the ratio of masses within radii which enclose two different overdensities. Previous numerical simulation analyses have shown that at a given redshift the halo sparsity carries cosmological information encoded in the halo mass profile. Moreover, its ensemble averaged value can be inferred from prior knowledge of the halo mass function at the overdensities of interest. Here, we present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…This kind of conversions is used in computing the sparsity of haloes (i.e. ratio of masses in two overdensities), which itself can probe cosmological parameters (Corasaniti et al 2018;Corasaniti & Rasera 2019) and dark energy models (Balmès et al 2014).…”
Section: Halo Masses Conversionmentioning
confidence: 99%
“…This kind of conversions is used in computing the sparsity of haloes (i.e. ratio of masses in two overdensities), which itself can probe cosmological parameters (Corasaniti et al 2018;Corasaniti & Rasera 2019) and dark energy models (Balmès et al 2014).…”
Section: Halo Masses Conversionmentioning
confidence: 99%
“…(2) holds valid to better than percent level (see e.g. Table 1 in Corasaniti & Rasera 2019). Hence, Eq.…”
Section: Halo Sparsitymentioning
confidence: 86%
“…The validity of Eq. (2) in predicting the ensemble average halo sparsity has been extensively tested using N-body halo catalogs from the RayGalGroupSims simulation of a ΛCDM model in Corasaniti et al (2018) and the halo catalogs from the MultiDark-Planck2 simulation in Corasaniti & Rasera (2019). These studies have shown that the simulation calibrated mass functions can predict the average halo sparsity to better then a few percent accuracy level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations